Far-red light photoacclimation in a desert Chroococcidiopsis strain with a reduced FaRLiP gene cluster and expression of its chlorophyll f synthase in space-resistant isolates - di Stefano, Giorgia; Battistuzzi, Mariano; La Rocca, Nicoletta; Selinger, Vera M.; Nürnberg, Dennis J.; Billi, Daniela (Frontiers in Microbiology, 2024)
Some cyanobacteria can use far-red light (FRL) to drive oxygenic photosynthesis, a phenomenon known as Far-Red Light Photoacclimation (FaRLiP). It can expand photosynthetically active radiation beyond the visible light (VL) range. Therefore, it holds promise for biotechnological applications, and may prove useful for the future human exploration of outer space. Typically, FaRLiP relies on a cluster of approximately 20 genes, encoding paralogs of the standard photosynthetic machinery. One of them, a highly divergent D1 gene known as chlF (or psbA4), is the synthase responsible for the formation of the FRL-absorbing chlorophyll f (Chl f) that is essential for FaRLiP. The minimum gene set required for this phenotype is unclear. The desert cyanobacterium Chroococcidiopsis sp. CCMEE 010 is unusual in being capable of FaRLiP with a reduced gene cluster (15 genes), and it lacks most of the genes encoding FR-Photosystem I. Here we investigated whether the reduced gene cluster is transcriptionally regulated by FRL and characterized the spectral changes that occur during the FaRLiP response of Chroococcidiopsis sp. CCMEE 010. All 15 FaRLiP genes were preferentially expressed under FRL, accompanied by a progressive red-shift of the photosynthetic absorption spectrum. In addition, the Chl f synthase from CCMEE 010 was heterologously expressed in two closely related desert Chroococcidiopsis strains. The transformants could be selected in both VL and FRL. Since the transformation hosts had been reported to survive outer space conditions, such an achievement lays the foundation towards novel cyanobacteria-based technologies to support human space exploration.